PENDIDIKAN LIBERALISME DALAM PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - Br, A. Nurhidayah; Harisah, Afifuddin (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2025)
ABSTRACT This study aims to examine the relationship between liberal education and Islamic educational philosophy, highlighting their points of convergence and divergence in the development of a contemporary Islamic education model in Indonesia. Through a qualitative approach and philosophical analysis, this research explores how the values of freedom of thought, rationality, and autonomy, which are characteristic of liberal education, can interact with the principles of monotheism, the integration of reason and revelation, and the cultivation of noble character within Islamic education. The findings indicate that while there are similarities in the emphasis on the development of rationality and intellectual freedom, there are fundamental differences in epistemological and axiological aspects, particularly concerning the role of revelation as a source of knowledge and moral boundaries within Islamic education. The primary challenges in integrating these two approaches include differing perceptions of individual freedom, curriculum design, teacher training, and social resistance to change. This research proposes a holistic model of Islamic education that is responsive to the dynamics of globalization while preserving its spiritual identity and Islamic values. The implications of this study are significant for the development of an adaptive, inclusive, and character-driven Islamic education system, aimed at preparing a generation capable of competing on a global scale without losing their spiritual and moral roots. ABSTRAK Penelitian ini bertujuan untuk mengkaji hubungan antara pendidikan liberalisme dan filsafat pendidikan Islam, dengan menyoroti titik temu dan perbedaan keduanya dalam pengembangan model pendidikan Islam kontemporer di Indonesia. Menggunakan pendekatan kualitatif dan metode analisis filosofis, penelitian ini mengeksplorasi bagaimana nilai-nilai kebebasan berpikir, rasionalitas, dan otonomi yang menjadi ciri khas pendidikan liberal dapat berinteraksi dengan prinsip-prinsip tauhid, integrasi akal dan wahyu, serta pembentukan akhlak mulia dalam pendidikan Islam. Temuan penelitian menunjukkan bahwa terdapat kesamaan pada penekanan pengembangan rasionalitas dan kebebasan intelektual, namun terdapat perbedaan mendasar dalam aspek epistemologi dan aksiologi, khususnya terkait peran wahyu sebagai sumber pengetahuan dan batasan moral dalam pendidikan Islam. Tantangan utama dalam integrasi kedua pendekatan ini meliputi perbedaan persepsi tentang kebebasan individu, desain kurikulum, pelatihan guru, dan adanya resistensi sosial terhadap perubahan. Penelitian ini menawarkan model pendidikan Islam yang holistik dan responsif terhadap dinamika globalisasi, namun tetap menjaga identitas spiritual dan nilai-nilai keislaman. Implikasi dari penelitian ini penting bagi pengembangan sistem pendidikan Islam yang adaptif, inklusif, dan berkarakter, guna menyiapkan generasi yang mampu berkompetisi secara global tanpa kehilangan akar spiritual dan moralnya.